Queirozia turbinata (Phyllactinieae, Erysiphaceae): a powdery mildew with a dematiaceous anamorph - Liberato, José R.; Barreto, Robert W.; Niinomi, Seiko; Takamatsu, Susumu (Mycological Research, 2006)
The powdery mildew monotypic genus Queirozia was reduced to a synonym of Pleochaeta in 1982. Now, a re-examination of the type material of Queirozia and of two other specimens showed that Queirozia turbinata has a very distinct combination of characters that do not allow its placement within Pleochaeta. It has forked special aerial hyphae, subclavate and predominantly lemon-shaped conidia, and both conidiophores and conidia varying from greyish to yellowish brown (a feature that appears to be unique for this fungus within the Erysiphales). This may represent the first dematiaceous anamorphic powdery mildew known to science. This fungus also has hemiendophytic mycelium, a character considered almost exclusive to the tribe Phyllactinieae. The outer wall surface pattern of wrinkled and turgid conidia of Q. turbinata as observed under the SEM is different from those presented in the literature for this tribe. Molecular analysis showed that Q. turbinata belongs to the tribe Phyllactinieae and is phylogenetic closer to Pleochaeta than to Leveillula or Phyllactinia. It is therefore acknowledged that Queirozia is closely related to Pleocheta but too distinct morphologically from this genus to be accepted as a synonym. Emended descriptions of Queirozia and Q. turbinata are presented.
Keywords: Ascomycota; Hyphomycetes; Molecular phylogenetics; Pleochaeta; Streptopodium